2017
DOI: 10.18196/ijnp.1264
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers of Cervical Cancer Screening Among Married Women in Minggir, Godean, Gamping Sub-Districts, Sleman District Yogyakarta

Abstract: Coverage of cervical cancer screening in Indonesia has only reached 5% and cervical cancer in Indonesia is still relatively high. The aimed of this cross-sectional study were to explore perceived barriers of cervical cancer screening and regular screening history among 384 married women in Sleman, Yogyakarta. Data were collected using modified questionnaire items from Champion Health Beliefs Model Scale. Results showed that only 13.8% of respondent have regular screening. Most of respondent in both group Regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…It showed that the role of the majority religious leaders was not present by 84%, community leaders did not exist by 87% and the role of health cares did not exist by 75%. In line with the study by Afsah (2017), exposure to health information will encourage early detection of cervical cancer. These data indicated that the factors influencing the behavior of early detection of cervical cancer are still very low, thus, cancer is found more often at advanced stage.…”
Section: Introductionmentioning
confidence: 75%
“…It showed that the role of the majority religious leaders was not present by 84%, community leaders did not exist by 87% and the role of health cares did not exist by 75%. In line with the study by Afsah (2017), exposure to health information will encourage early detection of cervical cancer. These data indicated that the factors influencing the behavior of early detection of cervical cancer are still very low, thus, cancer is found more often at advanced stage.…”
Section: Introductionmentioning
confidence: 75%
“…In initial conversations, women explained their disengagement with cervical cancer screening through such responses as 'Just because', 'Because I didn't want to', 'Because I didn't feel like it'. Some women referred to barriers to access such as feelings of embarrassment if the health professional was a man or pressure from male partners not to see male doctors (Afsah 2017;Islam et al 2017), but these issues were partial and ambiguous explanations. This suggested that something more complex was at play, requiring that we explore everyday social practices (not limited to health) and the historic reality of these structurally vulnerable communities.…”
Section: Methodological and Theoretical Approachesmentioning
confidence: 99%
“…Biaya untuk mengakses layanan skrining kanker serviks dapat menjadi penghambat bagi wanita dengan tingkat sosio-ekonomi yang rendah di negara berkembang 15,16,17,18,19 .…”
Section: Faktor Yang Mempengaruhi Cakupan Skrining Kanker Serviksunclassified